Faktor-Faktor Yang Berhubungan Dengan Kejadian Preeklamsia Di Rumah Sakit Bakti Timah Pangkalpinang Tahun 2024 - Nengsi Sapitri; Agustin; Ardiansyah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Pregnancy is a physiological process that brings changes to the mother and her environment. With pregnancy, a woman's body system experiences fundamental changes to support the development and growth of the fetus in the womb during a person's pregnancy process. Preeclampsia is a major cause of maternal and perinatal morbidity and mortality worldwide. In Indonesia, the incidence of preeclampsia is the second highest cause of maternal death after bleeding with a percentage of 25%. The aim of this research is to determine the factors associated with the incidence of preeclampsia at the Bakti Timah Pangkalpinang Hospital in 2022-2024. This study used a cross-sectional analytical observation study research design. The population in this study was 2,399 pregnant women at RSBT in 2022- 2023, with a sample of 59. This research was conducted in 09 December 2024-09 January 2025. Data analysis used the Chisquare test. The results of the analysis show that there is a significant relationship between maternal age with p-value = 0.028 POR= 3.989, history of hypertension with p-value = 0.000 POR = 15.938, Parity with p-value = 0.000 POR = 26.571 and obesity with p-value = 0.000 POR=19,333 with the incidence of preeclampsia. The conclusion of this study is that preeclampsia is caused by several factors, namely, age ≤20 years and ≥35 years, mothers who have a history of hypertension if their systolic pressure is ≤140 and diastolic pressure ≥90, mothers who experience parity more than 3 times and mothers who are obese with a BMI of more than 26, so there is a relationship between age, history of hypertension, parity and obesity with the incidence of preeclampsia in pregnant women at the Bakti Hospital. tin base pinang in 2024.